Use of electronic cigarettes among secondary and high school students from a socially disadvantaged rural area in Poland - Kaleta, Dorota; Wojtysiak, Piotr; Polańska, Kinga (BMC public health, 2016)
Background The use of e-cigarettes has been growing and has become a significant public health concern. Prevention of the youth access to, initiation and continuous use of e-cigarettes with special attention to vulnerable groups is a subject of a health debate. However, still little is known about characteristics of the underage e-cigarette users from different geographic and socio-economic backgrounds as well as other potential factors associated with the use of e-cigarettes, including simultaneous use with tobacco products or alcohol. The aim of the study was to investigate the prevalence and factors associated with ever and continued e-cigarette use among the secondary and high school students from a socially disadvantaged rural area in Poland. Methods The study sample consisted of 3552 students aged 13–19 years from Piotrkowski district. The anonymous, self-administered questionnaire adapted from the Global Youth Tobacco Survey was implemented to collect relevant information. The uni- and multivariate logistic regression analyses were applied to identify factors associated with ever, current (in the previous 30 days) and continued e-cigarette use. Results Almost 22 % of the sample reported ever e-cigarettes use and 27 % of the respondents indicated e-cigarettes use in the past month. Boys, in comparison with girls, were more likely to report current e-cigarette use (OR = 1.7; p < 0.001). Current e-cigarette use was strongly associated with alcohol consumption (OR = 4.3; p < 0.001), current (OR = 32.5; p < 0.001) and ever tobacco smoking (OR = 7.5; p < 0.001) as well as smoking parents (OR = 1.4; p < 0.05) and friends (OR = 4.5; p < 0.05). The use of e-cigarettes was also significantly associated with harm perception ( p < 0.001). A similar pattern was observed among ever e-cigarette users. Male gender (OR = 1.4; p < 0.05), current tobacco smoking (OR = 3.0; p < 0.01) and lack of knowledge about a ban on smoking in the school (OR = 1.4; p < 0.05) were predictors of the continued e-cigarette use. Higher paternal education (OR = 0.5; p < 0.001) and perception of e-cigarettes as more harmful comparing to tobacco (OR = 0.2; p < 0.001) protected from the continued e-cigarette use. Conclusions E-cigarette use is widespread in the investigated population, especially among boys, those with other risky behaviors and with smoking parents or friends. There is a need for further research and preventive policies to protect the youth from that exposure.